Planning A successful future : - Sestina, John E. (John Wiley and Sons, 2016)
A deeply insightful guide to goal-based financial planning and wealth management Planning a Successful Future&​nbsp;empowers advisors and clients to take control of their money and manage their income to achieve their financial goals. Written by the father of fee-only financial planning, this book features real-life stories and examples from over three decades in the industry to illustrate how financial planning works and the best way to create your strategy. You'll learn how to identify and prioritize your goals, and why they're important&​mdash;and how to get where you need to be for retirement, education, home ownership, and more. Practical exercises get you started on the right track, and useful checklists keep you organized and focused along the way. You'll get expert insight on risk management, allocation, tax reduction, estate planning, and more, as you develop your strategy and put it into action. The financial services industry undergoes frequent changes, and financial planning specifically is affected to a high degree. Keeping up with the latest news and distinguishing trend from legitimate methodology can itself be a fulltime job. This book gives you the background you need to create a plan, and make the smart choices that will help you grow and protect your wealth. Create a realistic and goal-based financial plan Take a more proactive approach to your finances Identify your goals and how to achieve them Allocate investments appropriately for your situation Financial planning is complex, with many variables to analyze and outside forces that can derail even the best laid plans. Planning a Successful Future gives you the information, tools, strategies, and insight you need to make the best decisions for your financial future